National Trust for Places of Historic Interest or Natural Beauty (U.S.) records - National Trust for Places of Historic Interest or Natural Beauty (U.S.)
Correspondence, minutes, reports, bylaws, constitution, and other records of a prvate organization concerned with historic preservation.
In part, typewritten transcripts.
Incorporated 1902 in Washington, D.C.; Carroll Davidson Wright, chairman. No records after 1904.
Collection material in English.
Keywords: Wright, Carroll Davidson, -- 1840-1909.; Historic preservation -- United States -- Societies, etc; Landscape protection -- United States -- Societies, etc